Developing a framework for a global comparative analysis of the governance of religious diversity. Issue 4 (8th August 2022) - Modood, Tariq; Sealy, Thomas
ABSTRACT: Between and within different world regions today religious diversity remains a significant challenge and researchers have identified a wide variety of church-state relations as well as of legal, institutional, and political arrangements related to state-religion connections. These variations in type and degree owe something to distinctive political, institutional, theological, and historical inheritances and have led to different normative conceptions of secularism and of state-religion relations and connections. This first contribution begins by mapping the ground of existing conceptions of secularism and state-religion connections. Our discussion first assesses normative approaches that emanate from 'the West' as well as from perspectives outside of 'the West' (such as India), and which might directly challenge the former. It then turns to outline a new framework of five modes of governance of religious diversity, presenting each in relation to a series of constitutive features or norms that characterise it and which distinguish it from other modes. This typology of modes forms the basis of the intra- and inter-regional comparative analyses presented in the regionally focused contributions to this collection. We finally provide an overview of these contributions and their application of the typology.